2014
DOI: 10.1016/j.febslet.2014.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of OCT4 by the ETS transcription factor PEA3 in NCCIT human embryonic carcinoma cells

Abstract: Edited by Ned ManteiKeywords: ETS family transcription factor Polyomavirus enhancer activator 3 OCT4 promoter Embryonic carcinoma NCCIT a b s t r a c tWe examined the molecular mechanism of OCT4 gene regulation by polyomavirus enhancer activator 3 (PEA3) in NCCIT cells. Endogenous PEA3 and OCT4 were significantly elevated in undifferentiated cells and reduced upon differentiation. PEA3 knockdown led to a reduction in OCT4 levels. OCT4 promoter activity was significantly up-regulated by dose-dependent PEA3 over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 56 publications
1
15
1
Order By: Relevance
“…Oct4 was also demonstrated to promote cell cycle progression in esophageal carcinoma (8), promote colony formation of glioma cells (9), and increase transmigration capacity in melanoma cells (10). These previous studies suggest that deregulation and dysfunction of Oct4 contribute to malignant establishment of a cancer stem cell phenotype (5).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Oct4 was also demonstrated to promote cell cycle progression in esophageal carcinoma (8), promote colony formation of glioma cells (9), and increase transmigration capacity in melanoma cells (10). These previous studies suggest that deregulation and dysfunction of Oct4 contribute to malignant establishment of a cancer stem cell phenotype (5).…”
Section: Introductionmentioning
confidence: 79%
“…For example, the expression of Oct4 was indicated to be significantly correlated with early hepatocellular carcinoma recurrence (4). Oct4 has been identified as overexpressed in human embryonic carcinoma (5), prostate cancer (6), and bladder cancer cells, and been associated with enhanced migration and invasion (7). Oct4 was also demonstrated to promote cell cycle progression in esophageal carcinoma (8), promote colony formation of glioma cells (9), and increase transmigration capacity in melanoma cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…38) We also previously reported that OCT4 and GDF3 are highly expressed in pluripotent human EC NCCIT cells and that this expression is reduced upon RA treatment in a time-dependent manner. 30,36,37,39,40) However, there is no report concerning the interaction between OCT4 and GDF3 at the transcriptional level. Therefore, to investigate their transcriptional relationship in pluripotent germ cell-derived EC cells, we first examined the expression of GDF3 and OCT4 in NCCIT cells during RA-mediated differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…34,35) Western Blot Analysis NCCIT cells were treated with RA for different amounts of time (0, 2, 4, 6, 8, 10 d) and harvested, or transfected with OCT4-targeting shRNA or the Flag-tagged OCT4 expression vector using the ViaFect transfection reagent (Promega) and harvested 48 h later. Western blotting was performed as previously described 36,37) with a minor modification. Membranes were blocked in 1% bovine serum albumin and incubated with anti-OCT4 polyclonal Each primary antibody-complexed membrane was further incubated with a horseradish peroxidase-conjugated secondary antibody (1 : 5000, Santa Cruz Biotechnology).…”
Section: )mentioning
confidence: 99%
“…Expression levels of CIC, ETV1, ETV4, ETV5, and WT1 were evaluated on both RNAseq platforms in comparison to other soft tissue tumors in each platform. The mRNA expression of known PEA3 family downstream target genes, including SPRY2, SPRY4, SPRED2, GPR20, DUSP6 GBX2, FGF8, POU5F1, MMP1/2/3/7/9, TWIST1, SNAI1/2, PTGS2, BAX, CCND2, ZEB1, PTK2, PLAU, ICAM1, VEGFA, NOTCH1, NOTCH4, and SPP1 was investigated from the whole transcriptome sequencing platform, while FRG1, PITX1, ZSCAN4, RFPL2, TRIM43, and LEUTX, were evaluated as DUX4 targets …”
Section: Methodsmentioning
confidence: 99%